Manajemen Sekolah dalam Pengelolaan Kegiatan Guru Bahasa Indonesa di Sekolah Dasar - Murni Yanto (ESTETIK : Jurnal Bahasa Indonesia, 2020)
The present study explained how the school management was in managingthe activities of Indonesia language teachers in elementary school. This wasa descriptive qualitative study. The subjects engaged were the principal, teachers, and elementary school committees. The data were garnered from interviews, observations and documentation. Subsequently, the data analysis used data reduction, data presentation, and drawing conclusion. The results of the current study showed that the school management in managing Indonesian elementary school teachers’ activities includes: a) The elementary school management in terms program planning has been carried out resting upon the objectives and the elementary school plans, but the involvement of the community (parents) in formulating elementary school programs is still lacking. b) The elementary school management in the fields of students, educators, education staff and curriculum has been implemented but not yet been in an appropriate way. c) The elementary school management in the field of leadership has analyzed the potential of the school, creating conducive elementary school. d) Elementary school management in the fields of supervision and evaluation, curriculum development, the empowerment of education and teachers, and supervision programs have not been adequate as expected.